Chinese herbal formula ruangan granule enhances the efficacy of entecavir to reverse advanced liver fibrosis/early cirrhosis in patients with chronic HBV infection: A multicenter, randomized clinical trial - Yufeng Xing; Weichao Zhong; Deti Peng; Zhiyi Han; Hua Zeng; Yanqing Wang; Lian Feng; Jinzhen Huang; Linyi Xu; Mingtai Chen; Daqiao Zhou; Kaiping Jiang; et al. (Elsevier, 2023)
Background: Nucleotide analogs treatment can reverse liver fibrosis in chronic hepatitis B (CHB). However, it has limited effect on fibrosis resolution in patients with CHB, particularly in preventing progression to hepatocellular carcinoma (HCC). Ruangan granule (RG), a Chinese herbal formula, has proven to produce a therapeutic effect against liver fibrosis in animal experiment. Thus, we aimed to evaluate the effect of our Chinese herbal formula (RG) combined with entecavir (ETV) to reverse advanced liver fibrosis/early cirrhosis from CHB. Methods: A total of 240 CHB patients with histologically confirmed advanced liver fibrosis/early cirrhosis from 12 centers were randomly and blindly allocated to consume either ETV (0.5 mg/day) plus RG (2 times/day) or control (ETV) for 48 weeks (wk) treatment. Changes in histopathology, serology and imageology were observed. Liver fibrosis reversion, defined as a reduction in the Knodell HAI score by ≥ 2 points and Ishak score by ≥ 1 grade, was assessed. Results: The rate of fibrosis regression and inflammation remission after 48 wk of treatment in histopathology was significantly higher in the ETV + RG group (38.73% vs. 23.94%, P = 0.031). The ultrasonic semiquantitative scores decreased by ≥ 2 points and were 41 (28.87%) and 15 (21.13%) in the ETV+RG and ETV groups, respectively (P = 0.026). The ETV+RG group had a significantly lower Fibrosis-4 score (FIB-4) index (P = 0.028). There was a significant difference between the ETV+RG and ETV groups in the liver function normalization rate (P < 0.01). Moreover, ETV plus RG combination treatment further reduced the risk of HCC in median 55-month follow-up (P < 0.01). Conclusions: This study illustrates that the Chinese herbal formula RG with ETV can improve advanced liver fibrosis/early cirrhosis regression in patients with CHB, further reducing the risk of HCC.